41BB-based and CD28-based CD123-redirected T-cells ablate human normal hematopoiesis in vivo. Issue 1 (10th June 2020) - Baroni, Matteo Libero; Sanchez Martinez, Diego; Gutierrez Aguera, Francisco; Roca Ho, Heleia; Castella, Maria; Zanetti, Samanta Romina; Velasco Hernandez, Talia; Diaz de la Guardia, Rafael; Castaño, Julio; Anguita, Eduardo; Vives, Susana; Nomdedeu, Josep; et al.
Abstract : Background: Acute myeloid leukemia (AML) is a hematopoietic malignancy which is biologically, phenotypically and genetically very heterogeneous. Outcome of patients with AML remains dismal, highlighting the need for improved, less toxic therapies. Chimeric antigen receptor T-cell (CART) immunotherapies for patients with refractory or relapse (R/R) AML are challenging because of the absence of a universal pan-AML target antigen and the shared expression of target antigens with normal hematopoietic stem/progenitor cells (HSPCs), which may lead to life-threating on-target/off-tumor cytotoxicity. CD33-redirected and CD123-redirected CARTs for AML are in advanced preclinical and clinical development, and they exhibit robust antileukemic activity. However, preclinical and clinical controversy exists on whether such CARTs are myeloablative. Methods: We set out to comparatively characterize in vitro and in vivo the efficacy and safety of 41BB-based and CD28-based CARCD123. We analyzed 97 diagnostic and relapse AML primary samples to investigate whether CD123 is a suitable immunotherapeutic target, and we used several xenograft models and in vitro assays to assess the myeloablative potential of our second-generation CD123 CARTs. Results: Here, we show that CD123 represents a bona fide target for AML and show that both 41BB-based and CD28-based CD123 CARTs are very efficient in eliminating both AML cell lines and primary cells in vitro and in vivo. However, both 41BB-based and CD28-based CD123 CARTs ablate normal human hematopoiesis and prevent the establishment of de novo hematopoietic reconstitution by targeting both immature and myeloid HSPCs. Conclusions: This study calls for caution when clinically implementing CD123 CARTs, encouraging its preferential use as a bridge to allo-HSCT in patients with R/R AML.